Augmented broadcaster identity-based broadcast encryption - Zhang, J.; Xu, Y.; Chen, Z. (Journal of Digital Information Management, 2013)
Identity-based Broadcast Encryption (IBBE) has the inherent key escrow problem that Private Key Generator (PKG) can fully determine the user's private key, which is an obstacle of the application of IBBE. The existing approaches to solving key escrow problem need the user to submit identity to multiple PKGs or interactions between PKG and the user in the private key extraction phase. For Point-to-Multipoint Identity-based Broadcast Encryption (P2MIBBE) that the computing capabilities of receiver are limited, these approaches are impracticable. We propose a new approach what we call Augmented Broadcaster Identity-based Broadcast Encryption (ABIBBE). It requires neither multiple PKGs nor calculation of receiver in the private key extraction phase. We construct a universal scheme to realize AB-IBBE, such that any IND-ID-CPA secure IBBE scheme can be extended to an IND-ID-CPA secure AB-IBBE scheme.
Keywords: Identity-based broadcast encryption; Key escrow

Froglingo, a programming language empowered by a total-recursive-equivalent data model - Xu, K.; Zhang, J.; Gao, S. (Journal of Digital Information Management, 2011)
The EP (Enterprise-Participant) data model is a language homomorphic to and semantically equivalent to a class of total recursive functions. It takes a unique position in the fields of programming languages and database management. Mathematically, it enables a programming language to achieve the greatest possible ease of use in software development and maintenance. (This assumes that a programming language incorporated with a higher expressive data model was easier than another one with a lower expressive data model, or no data model at all.) Practically, Froglingo - a programming language incorporated with the EP data model is a monolith that consolidates multiple software components of traditional software architecture. In addition, Froglingo is untyped, i.e., programmers write application programs without a necessity of user-defined types. Finally, Froglingo is a novel approach to many challenges facing traditional technologies, including feature scalability, user interface flexibility, and similarity. In this paper, we show with further clarity the concept of ease of use by proposing a mathematical definition for the concept of data models and by relating Froglingo with other programming language through the analysis of types and higher-order functions.
Keywords: EP data model; Froglingo programming langauge; Higher-order functions; Knowledge management; Total-recursive equivalence

A novel access control strategy for distributed data systems - Zhang, J.; Wang, X.; Liu, H.; Meng, J. (Journal of Digital Information Management, 2010)
It is one of the most important challenges to balance between security and scalability in large distributed data systems. In this paper, we introduce a new data distribution model, which is a generalized tree structure called as multitree. And its access control strategy is investigated. In our multitree data model, the database schema is expressed as a schema graph, and a database instance is imagined as a data graph. It is different from the traditional hierarchical data model, since a node in our multitree model can have many parent nodes. All the data graphs or schema are transformed into multitrees. The complex data relation of the distributed data systems is reduced based on graph theory. The complexity of distribution is decreased significantly. In the multitree model, each user has a maximum access range corresponding to its multitree. It is integrated naturally with security. We use organization structure to bound the data range that a user can access, and use roles to restrict the operations that the user can perform. The scalability of data distribution and access control administration are evaluated through the instance adapted from the TPC-C database. The results illustrates our data distribution model is helpful for the system to be resilient and scalable. It is suitable for large distributed system and cloud relational database.
Keywords: Access control; Cloud database; Data distribution; Multi-hierarchical model; Multitree